Participação dos neurônios orexinérgicos na resposta ventilatória ao CO2 - Silva, Eliandra Nunes da (Universidade Federal de São Carlos, 2023)
Orexinergic (OX) neurons, through the release of orexins, modulate several functions including sleep- wakefulness states and central chemoreception. OX receptors are expressed in regions involved in the control and modulation of the ventilatory response to CO2, such as the nucleus of the solitary tract (NTS) and the peduncle pontine tegmental nucleus (PPTg). In this study, we tested the hypothesis that orexinergic neurons stimulate the commissural nucleus of solitary tract (cNTS) and PPTg during central chemoreflex activation. Using a whole-body plethysmography system, our objective was to evaluate the ventilatory response to CO2 in Wistar rats during microdialysis of the OX-1R antagonist SB-334867 (5 mM) in the cNTS and PPTg. The experiments were carried out during the light and dark phases of diurnal cycle, and the microdialysis protocols in the cNTS were performed as follow: (1) hyperoxic normocapnia (0% CO2, 93% O2) and (2) hyperoxic hypercapnia (7% CO2, 93% or 50% O2), and microdialysis protocols in PPTg in: (1) normoxic normocapnia and (2) normoxic hypercapnia (7% CO2). We observed that OX-1R antagonism in NTSc and in NTgPP caused a significant attenuation in CO2 ventilatory responses compared to vehicle during wakefulness in the light phase of the diurnal cycle. Thus, our data suggest that orexinergic signaling contributes, via OX-1R in NTSc and NTgPP, to hypercapnic chemoreflex control during wakefulness in the light phase of the diurnal cycle.
Participation of orexinergic neurons in ventilatory response to CO2
Keywords: Quimiorrecepção central; Orexinas; Ciclo claro-escuro; NTS comissural; Núcleo tegmental pedúnculo pontino; Central chemoreception; Orexins; Light - dark cycle; Comissural nucleus of solitary tract; Peduncle pontine tegmental nucleus; CIENCIAS BIOLOGICAS::FISIOLOGIA